Palm oil and human health. Meeting report of NFI: Nutrition Foundation of Italy symposium. (18th August 2017) - Marangoni, Franca; Galli, Claudio; Ghiselli, Andrea; Lercker, Giovanni; La Vecchia, Carlo; Maffeis, Claudio; Agostoni, Carlo; Ballardini, Donatella; Brignoli, Ovidio; Faggiano, Pompilio; Giacco, Rosalba; Macca, Claudio; et al.
Abstract: The use of palm oil by the food industry is increasingly criticized, especially in Italy, for its purported negative effects on human health and environment. This paper summarizes the conclusions of a Symposium on this topic, gathered by the Nutrition Foundation of Italy, among experts representing a number of Italian Medical and Nutritional Scientific Societies. Toxicological and environmental issues were not considered. Participants agreed that: no evidence does exist on the specific health effects of palm oil consumption as compared to other saturated fatty acids-rich fats; the stereospecific distribution of saturated fatty acids in the triacylglycerol molecule of palm oil limits their absorption rate and metabolic effects; in agreement with International guidelines, saturated fatty acids intake should be kept <10% of total energy, within a balanced diet; within these limits, no effect of palm oil consumption on human health (and specifically on CVD or cancer risk) can be foreseen.